2012
DOI: 10.1017/s0954579411000757
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotionality and externalizing problems in toddlerhood: Overreactive parenting as a moderator of genetic influences

Abstract: The current study examined the interplay between parental overreactivity and children’s genetic backgrounds as inferred from birth parent characteristics on the development of negative emotionality during infancy, and in turn, to individual differences in externalizing problems in toddlerhood. The sample included 361 families linked through adoption (birth parents and adoptive families). Data were collected when the children were 9-, 18-, and 27-months old. Results indicated links between individual levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 77 publications
(142 reference statements)
2
36
0
4
Order By: Relevance
“…Com relação às características das crianças destacam-se os fatores de risco biológico como a prematuridade (Poehlmann et al, 2011), malformação ao nascimento (Blacher, Baker, & Kaladjian, 2013) e infecções congênitas (Swanson & Schleiss, 2013), além de fatores psicológicos, como o temperamento (Kim & Kochanska, 2012) e comportamento (Lipscomb et al, 2012). As características maternas, por sua vez, que infl uenciam essa interação são a responsividade, que se refere ao modo como o adulto altera seu comportamento e o ambiente físico em reposta às demandas da criança (Gartstein, Crawford, & Robertson, 2008;Kim & Kochanska, 2012), intrusividade, relativa à falta de respeito à autonomia da criança (Adam, Gunnar, & Tanaka, 2004;Taylor, Eisenberg, Spinrad, & Widaman, 2013), sincronia, defi nida como uma interação mutuamente regulada, harmoniosa e recíproca (Feldman, 2007;Gartstein et al, 2008) e depressão (Feng et al, 2008).…”
unclassified
“…Com relação às características das crianças destacam-se os fatores de risco biológico como a prematuridade (Poehlmann et al, 2011), malformação ao nascimento (Blacher, Baker, & Kaladjian, 2013) e infecções congênitas (Swanson & Schleiss, 2013), além de fatores psicológicos, como o temperamento (Kim & Kochanska, 2012) e comportamento (Lipscomb et al, 2012). As características maternas, por sua vez, que infl uenciam essa interação são a responsividade, que se refere ao modo como o adulto altera seu comportamento e o ambiente físico em reposta às demandas da criança (Gartstein, Crawford, & Robertson, 2008;Kim & Kochanska, 2012), intrusividade, relativa à falta de respeito à autonomia da criança (Adam, Gunnar, & Tanaka, 2004;Taylor, Eisenberg, Spinrad, & Widaman, 2013), sincronia, defi nida como uma interação mutuamente regulada, harmoniosa e recíproca (Feldman, 2007;Gartstein et al, 2008) e depressão (Feng et al, 2008).…”
unclassified
“…The role of temperamental negative emotionality in children’s externalizing and internalizing behavioral problems has been highlighted by researchers (e.g., Dougherty, Klein, Durbin, Hayden, & Olino, 2010; Lipscomb et al, 2012). Given that understanding the mechanisms or protective factors that might contribute to these relations are important, the primary goal of this study was to examine the mediating or moderating role of self-regulation in the relations of early childhood dispositional negative reactivity to children’s later behavior problems (i.e., conduct and generalized anxiety symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found moderation of birth mother anger/frustration on the link between adoptive parental harsh discipline (9 months) and infant anger/frustration (18 months; Rhoades et al 2009). Yet another study found moderation of externalizing problems at 3 years on the link between adoptive mother's over-reactive parenting (9 months) and infant negative emotionality (18 and 27 months), as well as moderation of birth mother negative emotionality on the association of adoptive mother's over-reactive parenting with the same outcome (Lipscomb et al 2012).…”
Section: Adoption Studiesmentioning
confidence: 96%